The determinants of bank default risk: Evidence from Hong Kong banks - Wu, Qiong (2019)
Stability is a crucial issue when concerning operating banks, and it is vital to avoid bank default. This study aims to measure the default risk of Hong Kong banks and identify the drivers of the probability of bank default. Boyd and Graham’s (1986) Z-score is calculated and use as the proxy for default. The empirical results based on a comprehensive dataset of 95 Hong Kong banks from 2012 to 2018. To undertake this analysis panel data regressions have been employed. Based on previous theoretical literature, we observe interbank financial ratios are the major predictors of bank default. The result of our model shows the return on average equity, cost to income, capital adequacy, and the inflation rate are variables which have impacts on the probability of bank default. } These findings encourage bankers, regulators and supervisors manage bank risk in advance to keep away from failures. It also highlights the fundamental importance of new international standards on risk management, which act as a fundamental based prevention tool to avoid further bank failures.